Effect of modified humic acid binder on pelletisation of specularite concentrates - Zhou, You-lian; Zhang, Yuan-bo; Liu, Bing-bing; Li, Guang-hui; Jiang, Tao (Journal of Central South University, 2015)
A modified humic acid (MHA) binder was tested as a substitute for bentonite to prepare qualified specularite pellets. The results show that there is stronger chemisorption between organic functional groups in MHA binder molecular and specularite particles, improving the green pellet strength. MHA binder has obvious effect on the strength and microstructure of preheated pellets due to the thermal decomposition of organic matters in MHA binder. Appropriately increasing preheating temperature or time can eliminate the adverse impact of organic matters on the preheated pellet strength. Compared with the bentonite pellets, the roasted pellets with MHA binder have a more compact microstructure, and the recrystallization of the Fe 2 O 3 crystal grains is better. Consequently, under optimal conditions, 0.75% (mass fraction) MHA binder pellets have equal or better pellet strengths and contain 1.06% more total iron than 2 % bentonite pellets. The testing results indicate that MHA binder is a promising and effective alternative to bentonite for the specularite pellets.